The probabilistic assessment of causality in the construction of railway vehicles - Prykhodko, V. I.; Bosov, O. O.; Myamlin, S. V. (Science and Transport Progress, 2008)
In the article the substantiation of existence of causconsequence relation between different elements of railway vehicles is presented. The probability assessment of mutual relation between technical conditions of separate elements is also presented.